Combined Surgical and Restorative Procedures to Treat Maxillary Canine with Gingival Recession and Cervical Wear - Dler Ali Khursheed; Faraedon Mostafa Zardawi (Hindawi Limited, 2022)
Introduction. Gingival recession (GR) with cervical tooth wear is a major concern for patients on the prominent maxillary canines, from both esthetic and dentine hypersensitivity points of view. Hypersensitivity could be treated nonsurgically; however, esthetics remain the major patients' concern that mostly requires surgical intervention for covering the denuded root surface. Several surgical procedures are applied successfully for covering single and multiple gingival recession; however, these procedures are sensitive procedures and not always predictable. Semilunar coronally repositioned flap (SCRF) is a very simple procedure that found to be very predictable for covering a single recession in presence of sufficient keratinized gingiva apical to the recession. The procedure provides better clinical outcome by involving less adjacent papillary tissue that maintains greater blood supply and achieves maximum flap stability with mattress sutures with minimal postoperative complications. Therefore, this case report is aimed at explaining the simplicity of this surgical procedure in the presence of wide keratinized tissue around the recession and starting the restorative procedure after a sufficient soft tissue healing period. Case Presentation. 42-year-old systemically healthy female patient referred with a single wide gingival type 1 (RT1) and cervical wear around tooth #43. A semilunar coronally repositioned flap was released and advanced coronally to cover the denuded root totally; then, the flap stabilized by three mattress sutures, and complete root coverage was achieved. Six months later, the cervical lesion was restored with composite filling material. Sixteen-month and 32-month postoperative follow-up revealed full coverage of the denuded root surface with firm stable gingiva; later, the gingiva in the area looked stable and healthy. Conclusion. Using SCRF in treating RT1 recession in the presence of wide keratinized gingiva is very promising surgical intervention for receded root coverage that requires less technical skill.